Pañjābī sohaja prakāsha, arthāta, Pañjābī muhāware, athāuntāṃ, bahu-arathaka shabada te gaṛagajja bole ādika dī piṭārī - Sāhiba Siṅgha, b. 1891 (SAMP early 20th-century Indian books project, 1941)
Dictionary of Panjabi proverbs and idioms.